2015
DOI: 10.1162/ajhe_a_00026
|View full text |Cite
|
Sign up to set email alerts
|

Inflated Responses in Measures of Self-Assessed Health

Abstract: Abstract/SummaryThis paper focuses on the self-reported responses given to survey questions of the form In general how would you rate your health? with typical response items being on a scale ranging from poor to excellent. Usually, the overwhelming majority of responses fall in either the middle category or the one immediately to the "right" of this (in the above example, good and very good). However, based on a wide range of other medical indicators, such favourable responses appear to paint an overly rosy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…Responses related to self-reported health status of surveyed individuals may not always correspond with the objective clinical condition of the individuals. In that sense, Greene et al (2015) have proposed a model to identify potential inflation of responses, i.e., whether people tend to report that their health is good or very good. In a random sample of Australian population they found around 10% probability of inaccurate reporting in the good and very good categories.…”
Section: Datamentioning
confidence: 99%
“…Responses related to self-reported health status of surveyed individuals may not always correspond with the objective clinical condition of the individuals. In that sense, Greene et al (2015) have proposed a model to identify potential inflation of responses, i.e., whether people tend to report that their health is good or very good. In a random sample of Australian population they found around 10% probability of inaccurate reporting in the good and very good categories.…”
Section: Datamentioning
confidence: 99%
“…Labor studies suggest that individuals may underreport health as poor health is viewed as a socially acceptable explanation for not working or for limited labor supply (Bound 1991;Bound, Brown, and Mathiowetz 2001;Currie and Madrian 1999). On the other hand, recent work by Greene, Harris, and Hollingsworth (2015) suggests a somewhat more nuanced pattern of reporting error in self-reported general health. For example, using the 5-point scale that we study, the authors document a tendency of respondents to report their general health as "good" or "very good" (i.e., the middle response and the response one "to the right" of the middle response on a 5-point scale).…”
Section: B Outcome Variablesmentioning
confidence: 99%
“…However, to the best of our knowledge, it is not possible to accurately sign the bias for our continuous self-reported health variables. 21 The econometrics methods designed to account for reporting error in self-reported health rely on access to panel data (i.e., repeated observations on the individuals providing selfreported health), instrumental variables in the case of mismeasured right-hand-side variables, or survey design techniques in contingent valuation and other stated preferences studies (Bound, Brown, and Mathiowetz 2001;Greene, Harris, and Hollingsworth 2015;Maclean et al 2015). Given that we rely on the BRFSS, which is composed of repeated cross sections and is an observational study collected by the CDC, and the self-reported variables are our dependent variables, such methods are unfortunately not available to us.…”
Section: B Outcome Variablesmentioning
confidence: 99%
“…Important issues are the existence of systematic differences in how individuals assess their health and report it on an ordinal scale, and how this reporting heterogeneity could obscure true health inequalities (Kerkhofs and Lindeboom, 1995;Lindeboom and Van Doorslaer, 2004;Etilé and Milcent, 2006;Bago d'Uva et al, 2011;Layes et al, 2012;Greene et al 2015). For example, Bago d'Uva et al (2011) find no socioeconomic inequality in visits to the doctor when SAH is used to measure health need, but after correcting SAH for reporting heterogeneity, that inequality favours the moreeducated.…”
Section: Discussionmentioning
confidence: 99%